Lower Gasrointestinal Tract Bleeding Caused by Inflammatory Pseudotumour in Meckel’s Diverticulum: Report of A Case (Annals of Medical Research, 2021)
None
Keywords: Inflammatory pseudotumour, Meckel’s diverticulum, Bleeding